Implementasi Dongeng Digital Penguatan Profil Pembelajaran Pancasila melalui Project Based Learning - Taelagat, Rencia Renty (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This study investigates the implementation of digital storytelling as an approach to strengthen the profile of Pancasila education through Project Based Learning (PBL). A quantitative method with an experimental design was used to compare the effectiveness of learning between the experimental group using digital storytelling with PBL and the control group using traditional teaching methods. The sample consisted of 100 fifth-grade students in Surabaya. Data were collected through written tests and questionnaires before and after the intervention. The results showed a significant improvement in students' understanding and interest in Pancasila values in the experimental group